Determinants Of Survival Among Patients with Cervical Cancer: A Hospital Based Study - Kaverappa, Vishma B; Boralingaiah, Prakash; Kulkarni, Praveen; Manjunath, Renuka (National Journal of Community Medicine, 2015)
Introduction: Cervical cancer is the fourth most common cancer among women worldwide and India contributes largest propor- tion to it. As per Globacon 2012 there were 1,23,000 cases and 67,000 deaths due to cervical cancer in India. Studies directed to- wards identifying the factors determining survival will help poli- cy makers in designing the strategies for prolonging the life of these patients. Objective of the study was to assess the factors de- termining survival among patients with cervical cancer. Methodology: This combined prospective and retrospective study was conducted during January 2012- December 2012 (One year) among all the newly diagnosed cases of cervical cancer from January 2006 to December 2007 at a tertiary care cancer hospital. Baseline data was collected by reviewing the medical records and cases were followed up for the next five years from the date of diagnosis to assess their survival status. Results: Among 380 patients included in the study, overall five year survival rate was found to be 48.1%, 38.7% had lost their life and 13.2 % lost to follow up. Age at diagnosis, education, perfor- mance status at presentation, staging (p = 0.001), parity, tobacco chewing (p< 0.01) and age at menopause (p = 0.05) were signifi- cantly associated with survival. Conclusion: Five year survival rate for cervical cancer was found to be 48.1%. Various factors determining survival were potentially modifiable.